HEMOCYTES IN SCORPION – HETEROMETRUS PHIPSONI - A. E. PATIL; U. H. SHAH (The Bioscan, 2013)
Seven types of hemocytes have been identified in the hemolymph of scorpion Heterometrus phipsoni by light and phase contrast microscope: prohemocyte (PR)- 4%, plasmocyte (PL)- 79%, granulocyte (GR)- 11%, sherulocyte (SP)- 2%, adipohemocyte (AD)- 1%,oenocytoid (OE)- 2%, coagulocyte (CO)- 1%. The PR was smallest with large nucleus, PL was polymorphic and abundant. The GR was abundant with cytoplasmic granules, SP was large with spherules. The AD was with variable in size and shape, OE was with less cytoplasmic organelles while CO was very fragile hemocytes. Along with morphology Total and Differential Hemocytes Count (THC and DHC) was also calculated in present investigation. The values of THC were 19500/mm3 in male, 9600/mm3in non-pregnant female while 11050/mm3 in pregnant female.